THE NATURES OF ZINC SULFIDE CONCENTRATES AND ITS BEHAVIOR AFTER ROASTING PROCESS - Dessy Amalia; Tatang Wahyudi; Yuhelda Dahlan (Puslitbang tekMIRA, 2018)
The sample used for this study was a sulfide flotation concentrate that came from PT Lumbung Mineral Sentosa.The phase changes that occur in the particles of zinc sulfide concentrate during roasting in a muffle furnace were investigated using light microscopy, X-ray diffraction (XRD), and Scanning Electron Microscopy (SEM) with Energy Dispersive Spectroscopy (EDS) while its chemical composition was analyzed using atomic absorption spectroscopy (AAS) and X-ray fluorescence (XRF) methods. Characterization also employed DTA-TGA instrument to provide data on the transformations that have occurred while the TGA data presents information about physical and chemical phenomena. Mineral composition of the sample included sphalerite, galena, chalcopyrite, and pyrite. Sphalerite was the most dominant one. Roasting sphalerite samples was intended to release the sulfur from its sulfide, Such a release was made easier for further treatment of the zinc such as a leaching process. Roasting temperature varied from 200 - 1,100 °C. Sphalerite starts to change when the temperature was raised to 650 °C performing the formation of zincite, franklinite, quartz and sphalerite as well. This composition did not change although the temperature increased to 1,100 °C. The Zn content within the original sample was 59.00% and then increased with the increasing of temperature but the improved in line with the increased temperature. The highest Zn was 78.98% achieved at 1,100 °C.